SHOBHA DE: THE DOYENNE OF ‘POPULAR CULTURE’ IN INDIAN ENGLISH LITERATURE - Kanhaiya Kumar Sinha (Universitas Negeri Yogyakarta, 2024)
Literature has long been a vital part of society, and Indian women have significantly contributed to this field. Their remarkable achievements in literature are widely recognised and appreciated. Women, known for their creativity and artistic flair, have a profound connection with literature, which demands considerable artistic imagination. Indian women novelists, in particular, have added a fresh dimension to Indian English literature. This paper explores the evolving trends in Indian English writing, focusing specifically on Shobha De. It provides an in-depth analysis of her fiction, with particular attention to her incorporation of ‘Popular Culture,’ and highlights how her works diverge from other novelists in introducing this element into Indian English literature.